The Effect of Pairing Individuals With Different Social Skills on Interpersonal Motor Coordination - Mukai, Kae; Miura, Akito; Kudo, Kazutoshi; Tsutsui, Seijiro (Frontiers in Psychology, 2018)
Previous studies have demonstrated that combining individuals with different social skills affects performance in rhythmic interpersonal motor coordination, with individuals with lower social skills, such as individuals with autism spectrum disorder or schizophrenia, being found to follow the actions of partners with higher social skills. In this study, we investigated whether this finding could be generalized among pairs of individuals without disability. To perform this, we applied an interpersonal motor coordination task that required participants to perform rhythmic movements featuring an interpersonal relative phase pattern of 90°. We did not assign the two roles (i.e., the preceding and following roles) to the participants, meaning they were forced to determine which roles to adopt by observing each other’s movements, without verbal communication. Individual social skills were measured using the Autism-Spectrum Quotient (AQ). We found that pairs of participants with widely differing AQ scores performed better than did pairs with similar AQ scores. Most notably, the participants with higher AQ scores tended to precede their partners in the present task, which is the opposite result to that reported in previous studies. Our findings suggest that paring individuals without disability according to their social skills influences their interpersonal coordination performance in tasks wherein they must determine the preceding and following roles themselves.